Feasibility of the Lee Silverman Voice Treatment-BIG Intervention in Stroke. (January 2021) - Proffitt, Rachel; Henderson, Whitney; Stupps, Mikayla; Binder, Lisa; Irlmeier, Bethany; Knapp, Erin
Lee Silverman Voice Treatment-BIG (LSVT BIG) has been used in Parkinson's disease and in two case studies with individuals post-stroke. The purpose of this study was to examine the feasibility, acceptability, and preliminary clinical effect of the LSVT BIG program for individuals post-stroke. This study was a waitlist crossover design. Outcomes were assessed at baseline, after 4 weeks, and after crossover. The primary outcomes were feasibility and acceptability; clinical outcomes were also assessed. We contacted 888 potential participants. Of the 35% of individuals who were interested in the study, most were ineligible to participate because they lacked transportation to the clinic. Five individuals were eligible and enrolled in the study. All completed 100% of in-clinic sessions. Four participants rated their occupational performance higher after the LSVT BIG intervention. It is feasible to deliver the LSVT BIG in the chronic stroke population. Individuals who complete the protocol demonstrate clinically relevant improvements.